Detection of Listeria monocytogenes in foods - Ponniah, Jeyaletchumi; Robin, Tunung; Paie, Margaret Selina; Radu, Son; Mohamad Ghazali, Farinazleen; Cheah, Yoke Kqueen (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2010)
Listeria monocytogenes is a gram positive, facultative intracellular pathogen with the capacity to cause food poisoning outbreaks as well as severe illness in vulnerable human population groups. It can cause a rare but serious disease called listeriosis with high fatality rates (20–30%) compared with other foodborne microbial pathogens. Although Listeria monocytogenes is infective to all human population groups, it is more likely to cause severe problems among pregnant women, immunocompromised individuals, the elderly and neonates. There are a variety of phenotyphic and genotyphic methods for the detection of Listeria monocytogenes in foods. Recent technological advances have increased the ability of scientists to detect Listeria monocytogenes. The purpose of this review is to discuss molecular characteristics of the Listeria monocytogenes pathogen, standard detection methods of this pathogen in foods based on culture methods, confirmation of species and subtyping based on phenotypic and genotyphic methods.